Crisis and transformation : the kibbutz at century's end - Ben Rafael, Eliezer (SUNY series in Israeli studies., 1997)
This book examines kibbutz life following the Israeli economic crisis of 1985, focusing on the kibbutz's dramatic transformation from a well-defined social structure to a collective identified principally by its cultural preoccupations. It centers on the contradictions endemic to kibbutz identity. Ben-Rafael shows how the crisis brought together a general pro-change Zeitgeist with the interests of the kibbutz's stronger social segments and individuals to produce widespread changes and the fragmentation of kibbutz reality as a whole. The book's findings are based on a large-scale research investigation (1991-1994) headed up by Ben-Rafael that included twenty research studies and involved the participation of researchers from diverse social-science disciplines. The book also provides a statistical abstract and a comprehensive kibbutz bibliography.